Hepatic injury and metabolic perturbations in mice exposed to perfluorodecanoic acid revealed by metabolomics and lipidomics - Lvyun Sun; Shuling He; Jiali Chen; Amei Su; Qiuyao Mao; Wenyuan Zhang; Ying Pan; Jiaqian Hu; Disheng Feng; Yang Ouyang (Ecotoxicology and Environmental Safety)
Perfluorodecanoic acid (PFDA) is a typical perfluoroalkyl substances frequently encountered in populations, posing significant risks to human health. However, research on the effects of PFDA exposure on organism metabolism and related pathogenic mechanisms is severely lacking. In this study, serum and liver samples of C57BL/6 J mice exposed to different doses of PFDA were analyzed by UPLC-HRMS-based metabolomics and lipidomics techniques. Both 1 mg/kg and 10 mg/kg PFDA exposure induced liver damage, while only 10 mg/kg PFDA exposure caused weight loss. Metabolomics analysis revealed that 330 and 515 metabolites were significantly altered in the serum and liver of mice after PFDA exposure, respectively. Most amino acids and peptides increased in the serum but decreased in the liver. Lipidomics analysis indicated that 281 and 408 lipids experienced significant alterations in the serum and liver after PFDA exposure, respectively. Most lipids, particularly multiple triacylglycerols, were downregulated in a dose-dependent manner in both serum and liver. Taken together, PFDA can induce changes in the amino acid metabolism pathway, disrupt fatty acid β-oxidation, and down-regulate glycolipid pathways in mice, resulting in disturbances in energy metabolism. These findings suggested that the liver is a critical target organ for PFDA exposure, and will also help inform future risk assessment.